Byrne_et_al_Harvest_data - Byrne, Michael; Cortes, Enric; Vaudo, Jeremy; Harvey, Guy; Sampson, Mark; Wetherbee, Bradley; Shivji, Mahmood (Dryad Digital Repository, 2017)
Information on all harvest events